Diagnostic impact of percutaneous renal biopsy - Kitterer, Daniel; Guerzing, Katharina; Segerer, Stephan; Alscher, M. Dominik; Amann, Kerstin Ute; Braun, Niko; Latus, Joerg (Clinical Nephrology, 2015)
Ultrasound-guided percutaneous renal biopsy (PRB) is an important diagnostic tool for nephrologists. Athough widely used and without question of pivotal importance for the diagnosis of renal diseases, little systematic data regarding standardized indications, outcomes, or consequences for this procedure are available. The aim of this study was to compare the clinically suspected diagnosis with the morphological results and the potential impact of PRB on the treatment of the patient.205 patients who underwent PRB of the native kidney within a 4-year period were included in this retrospective analysis. The biopsy results (BR), discharge diagnosis (DD), and the suspected diagnoses (SD) of the attending nephrologists prior to biopsy were documented.Mean age of the patients was 58 (range 44 - 77) years. The majority of patients (61%) received PRB during an acute disease phase, whereas 39% had elective PRB. Percutaneous biopsy of the native kidney led to a discharge diagnosis in 92% of the patients, with low complication rates (with 3 out of 205 patients had major bleeding complications). In 2/3, the nephrologists were correct with the suspected diagnosis prior to the biopsy. In 74% of the biopsies, a disease was identified that was potentially responsive to treatment modification.In summary, PRB was found to be a safe procedure that confirmed the suspected clinical diagnosis in two thirds of patients. As one third of the histopathological analyses demonstrated a non-suspected disease, the biopsies were of major importance for the correct treatment of the patients.
EVALuna2:25522